Central Banking Legislation Volume 2 : A Collection of Central Bank, Monerary and Bankin Law, Volume II. (International Monetary Fund, 2003)
This paper discusses the central banking, monetary, and banking laws for 17 countries in Europe, an area where many of the techniques that are now universally used in regulating or controlling the supply of money and credit were developed. The complete text of the basic central bank law of each country is given, as well as the by-laws of the central bank where they supplement major provisions of the basic law, and subsidiary legislation where pertinent. General banking laws are in most instances presented in summary form.